Current Endovascular Treatment of Abdominal Aortic Aneurysms. - Hakaim, Albert G. (John Wiley & Sons, 2007)
Rupture of an abdominal aortic aneurysm is one of the leading causes of death. The risk of rupture has been a controversial topic for years and only recently have population-based studies provided better evidence for clinical management. This book includes material by an internationally renowned group of authorities directed by a prominent vascular surgeon at Mayo Clinic. The contents represent a well-balanced clinical endovascular approach to the exciting area of vascular medicine and surgery. "We are living in a period of exciting transformation. The message for anyone interested in the trea.